2015
DOI: 10.1016/j.ijbiomac.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and cytotoxicity of N,N,N-trimethyl chitosan/alginate beads containing gold nanoparticles

Abstract: Polyelectrolyte complex beads based on N,N,N-trimethyl chitosan (TMC) and sodium alginate (ALG) were obtained. This biomaterial was characterised by FTIR, TGA/DTG, DSC and SEM analysis. The good properties of polyelectrolyte complex hydrogel beads were associated, for the first time, with gold nanoparticles (AuNPs). Through a straightforward methodology, AuNPs were encapsulated into the beads. The in vitro cytotoxicity assays on the Caco-2 colon cancer cells and healthy VERO cells showed that the beads present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 23 publications
(33 reference statements)
0
30
0
Order By: Relevance
“…Sodium alginate (ALG) was purchased from Across Organics (NJ, USA) and the ratio of mannuronic acid to guluronic acid (M/G) of the ALG was 1.56, as stated by the manufacturer. It has already been reported that the values of the average number (Mn) and average-weight (Mw) molecular weights for this alginate are 339,000 g mol −1 and 1,073,000 g mol −1 , respectively [22]. Silver nitrate, sodium citrate, potassium dihydrogen phosphate and acetic acid were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium alginate (ALG) was purchased from Across Organics (NJ, USA) and the ratio of mannuronic acid to guluronic acid (M/G) of the ALG was 1.56, as stated by the manufacturer. It has already been reported that the values of the average number (Mn) and average-weight (Mw) molecular weights for this alginate are 339,000 g mol −1 and 1,073,000 g mol −1 , respectively [22]. Silver nitrate, sodium citrate, potassium dihydrogen phosphate and acetic acid were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology employed for the preparation of beads was based on the method published by Martins et al [21,22,24]. Scheme 1 depicts the preparation of beads based on TMC/ALG.…”
Section: Beads Preparation and Silver Nanoparticles Loadingmentioning
confidence: 99%
“…For the cancerous cells, AuNPs are being utilized as salutary and incongruous agent for cancer disclosure. NPs have charged surface that can fasten arbitrarily to biological molecules through the electrostatic interactions [25]. For the configuration of electrochemical and other types of biosensors, nanoparticle-based materials are used as they give the great sensitivity and specificity.…”
Section: A Rt I C L E I N F O Abstractmentioning
confidence: 99%
“…The resonance signal at ı 2.05 ppm presented in the CHT 1 H NMR spectrum (Fig. 1a) was assigned to the hydrogen atoms of acetylated residues; the resonance at ı 3.16 ppm was assigned to the hydrogen atoms (H2); the resonances observed between ı 3.61 and ı 4.45 ppm were assigned to the hydrogen atoms (H3-H6) and resonances of low intensity that occur in the spectral range between ı 4.5 and ı 5.5 ppm were assigned to the hydrogen atoms (H1) [28][29][30]. However, the intense resonance in the spectral range ı 4.72 to ı 5.00 was attributed to hydrogen resonance of water molecules.…”
Section: Characterization Of Nn-dimethyl Chitosan By 1 H Nmrmentioning
confidence: 99%
“…DMC was obtained with dimethylation degree (DD) of ca. 86% [30,31]. The DD was obtained using Eq (1), from the area attributed to resonance of hydrogen atoms on N-dimethylated sites N(CH 3 ) 2 , at ı 3.10 ppm, and from area of H2 resonance at ı 3.43 ppm (Fig.…”
Section: Characterization Of Nn-dimethyl Chitosan By 1 H Nmrmentioning
confidence: 99%